2015
DOI: 10.17221/8237-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Male pronucleus formation after ICSI: effect of oocyte cysteine or sperm Triton X-100 treatments

Abstract: ABSTRACT:In pigs, intracytoplasmic sperm injection (ICSI) efficiency is still poor. The inadequate decondensation of the sperm chromatin, its transformation into the male pronucleus (MPN) together with the subsequent inability to activate the oocyte, seem to be the main causes of the low ICSI efficiency. In order to improve the MPN formation we took two different approaches. On the one hand, the in vitro culture (IVC) medium post-ICSI was supplemented with 1.71mM cysteine (CYS). Alternatively, the sperm membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
(87 reference statements)
1
0
0
Order By: Relevance
“…Therefore, the IVF method selection, sperm and oocyte factors could have detrimental effects on the fertilization and ED potential. In agreement to our results, another study reported that reduced oocyte activation and male PN formation are the main causes of low ICSI efficiency [ 69 ]. Results obtained in the present study demonstrate that less PN formation (non-fertilized oocytes) is obtained after ICSI compared to IVF and PICSI.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the IVF method selection, sperm and oocyte factors could have detrimental effects on the fertilization and ED potential. In agreement to our results, another study reported that reduced oocyte activation and male PN formation are the main causes of low ICSI efficiency [ 69 ]. Results obtained in the present study demonstrate that less PN formation (non-fertilized oocytes) is obtained after ICSI compared to IVF and PICSI.…”
Section: Discussionsupporting
confidence: 93%